2015
DOI: 10.1111/cote.12163
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of novel regenerated cellulosic, viscose, and cotton fibres and the dyeing properties of fabrics

Abstract: There is a global demand for constant increase in the production of textile fibres. Currently, the market for cellulosic fibres is dominated by cotton and viscose fibres. However, new alternative cellulosic fibres are being sought to meet the growing demand. The dyeing properties of novel fibres aiming at the marketplace are among the properties that determine their applicability to textiles. Recently, a novel process for producing cellulosic fibres, the Biocelsol process, has been scaled up so that the spinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…2 Kamppuri et al found viscose to have a higher water adsorption capacity than cotton, giving the larger pore size of viscose fibers as a possible reason for this. 13 Abu-Rous et al suggested moisture-related properties of viscose in part accounted for the intensity of odor volatiles (and microorganisms) on worn t-shirts. 14 With a possible greater capacity to hold water, the fiber would also have a higher capacity to bind/hold other polar compounds.…”
Section: Adsorptionmentioning
confidence: 99%
“…2 Kamppuri et al found viscose to have a higher water adsorption capacity than cotton, giving the larger pore size of viscose fibers as a possible reason for this. 13 Abu-Rous et al suggested moisture-related properties of viscose in part accounted for the intensity of odor volatiles (and microorganisms) on worn t-shirts. 14 With a possible greater capacity to hold water, the fiber would also have a higher capacity to bind/hold other polar compounds.…”
Section: Adsorptionmentioning
confidence: 99%
“…The reason behind this trend might be the possession of more hydroxyl (-OH) groups in the henna dye, which is the basic unit to provide shade depth; therefore, henna dyed fabric showing higher K/S values (Kamal Alebeid and Zhao, 2017). Herein viscose fabric overall showed increased K/S values than cotton fabric; the reason behind might be more absorbivity in formar than latter (Kamppuri et al, 2015).…”
Section: Antibacterial Printing Of Cellulosic Fabricsmentioning
confidence: 83%
“…Furthermore, the absence of the peak at 1111 cm –1 is a characteristic present in this type of cellulose [ 12 , 27 ]. For cellulose I, the band corresponding to the β-glucosidic bonds is present at 897 cm −1 ; for the spectrum of the analyzed viscose, this peak is found at 891 cm −1 , as is characteristic [ 28 ]. Based on these results, there is no notable difference between the absorptions of the two viscose products, and that, in both cases, the cellulose II structure predominates.…”
Section: Resultsmentioning
confidence: 99%